The elegant courtly life of the tea witch. 1 - Kaeruda, Ameko; Yorifuji (The elegant courtly life of the tea witch, 2024)
"At the royal court, the weakest mage is the tea witch, who uses their powers to make tea for the noble lords and ladies... but Remy has some incredible powers that will result in all kinds of courtly intrigue! The first volume in a heart-warming and cosy ongoing series, The Elegant Courtly Life of a Tea Witch tells the tale of Remy, a lowly tea witch using her magic to brew the finest cuppa for the noble lords and ladies. All she really wants is a quiet life creating gorgeous displays for shop windows... but she's slowly drawn into a world of intrigue as her incredible powers of transformation make her the gossip of the court... and the object of affection for a naïve princess!" -- Amazon.com.